'The gleaming mane of the serpent': the Birka dragonhead from Black Earth Harbour. (June 2018) - Kalmring, Sven; Holmquist, Lena
Abstract: Abstract : The 'Birka dragon' symbol is synonymous with the famous Viking Age town of that name, an association born from the 1887 discovery of a casting mould depicting a dragonhead. Recent excavations in Black Earth Harbour at Birka have yielded a dress pin that can, almost 150 years later, be directly linked to this mould. This artefact introduces a unique 'Birka style' to the small corpus of known Viking Age dragonhead dress pins. The authors discuss and explore the artefact's manufacture, function and chronology, and its connections to ship figureheads.